Enhancing the ecological validity of the Beads Task as a behavioral measure of intolerance of uncertainty. (June 2016) - Jacoby, Ryan J.; Abramowitz, Jonathan S.; Reuman, Lillian; Blakey, Shannon M.
Highlights: Aimed to enhance ecological validity of the Beads Task as an in vivo measure of IU. Incorrect Beads Task decisions were paired with the Cold Pressor Task (CPT). Beads Task importance and distress ratings were elevated relative to previous work. CPT pain tolerance was inversely associated with later Beads Task distress. In vivo Beads Task distress was uniquely correlated with self-report inhibitory IU Abstract: To broaden the measurement of intolerance of uncertainty (IU) beyond self-report methods, recent research has examined the Beads Task as a behavioral measure of IU. In the present study, we enhanced this task to increase its ecological validity by maximizing decisional uncertainty and the importance of a correct response. Undergraduate participants ( n  = 102) completed the Beads Task with instructions that they would complete the Cold Pressor Task (CPT) if they answered incorrectly. As hypothesized, baseline CPT endurance time and self-reported pain level were weakly associated with later Beads Task distress during the decision-making process. Furthermore, in vivo Beads Task distress was associated with self-report inhibitory IU, which measures avoidance and paralysis in the face of uncertainty, but not with prospective IU, perfectionism, or general psychological distress after making statistical adjustments for multiple comparisons. Comparisons to previous work using the Beads Task, clinical implications, and avenues for future research are discussed.